THE INFLUENCE OF SUBSTRATE NUTRIENT CONTENT ON THE DENSITY OF SEAGRASS (Enhalus acoroides) IN THE WATERS OF THE ISLAND OF PONCAN, NORTH SUMATRA PROVINCE - Ellysa Shintya; Thamrin Thamrin; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in April-May 2019 in the waters of Poncan Island, North Sumatra Province, which aims to determine the large nutrient content of substrate (nitrate and phosphate), the level of seagrass density Enhalus acoroides, and to determine the effect of nutrient content of the substrate on the density of seagrass Enhalus acoroides. Determination of the research station by purposive sampling and research sampling using the transect line method. The results showed that the highest nutrient content of substrate (nitrate and phosphate) was found at Station II which has a type of muddy sand substrate and the area is influenced by tourist activity.Nitrate concentration values were 0,074 mg / l and 0,122 mg / l for phosphate concentration values.The highest seagrass density was in Station II with a value of 74,22 stands / m2which had the highest nitrate and phosphate content, and the lowest seagrass density was in Station III which had the lowest nitrate and phosphate concentrations.Simple linear regression test results of the influence of nutrient substrate on the density of seagrass with a value of R2(coefficient of determination) = 0,27 (nitrate), 0,40 (phosphate) indicates there was effect of nitrate and phosphate on the density of seagrass Enhalus acoroides. Keyword: Nutrient Substrate, Nitrate and Phosphate, Seagrass Density